Method for developing catalogs focused on facilitating the implementation of best practices for project management of software development in SMEs [Método para el desarrollo de catálogos enfocados en facilitar la implementación de buenas prácticas para gestión de proyectos de desarrollo de software en PyMEs] (2017)
Software development industry is a key factor in the worldwide economy. In Mexico, this sector consists mostly of small and medium enterprises (SMEs) and they represent the 99% of the business software industry. This highlights the importance of implementing best practices in software engineering SMEs to ensure continuous improvement. In this context, there are several models, methodologies and standards that contain best practices focused on improving software development processes such as CMMI-DEV v1.3, ISO 12207, ISO 15504, etc. However, to implement it in SMEs they should be tailored according to the organization size and type of business. Therefore, SMEs require the use of techniques and tools that help them implementing the best practices. This paper aims to present a proposal of a method for creating catalogs of tools and techniques related to software development project management, specifically in risk management, that will provides a set of techniques and tools than an SME can select according to its specific needs in order of facilitate the implementation of best practices. © 2017 IEEE.